Effect of multiple, simultaneous vaccines on polio seroresponse and associated health outcomes. Issue 24 (4th June 2015) - Broderick, Michael P.; Oberste, M. Steven; Moore, Deborah; Romero-Steiner, Sandra; Hansen, Christian J.; Faix, Dennis J.
Highlights: Polio (IPV) vaccination alone or simultaneously with one other vaccine was compared to vaccination with polio and four other vaccines. IPV alone or with one other vaccine was associated with a lower proportion of polio seroconversions than IPV in combination with 4 other vaccines. There was no difference between IPV alone or with one other vaccine than IPV in combination with 4 other vaccines with respect to healthcare encounters over one a one-year period. Abstract: Background: Administration of multiple simultaneous vaccines to infants, children, and military recruits is not uncommon. However, little research exists to examine associated serological and health effects, especially in adults. Method: We retrospectively examined 416 paired serum specimens from U.S. military subjects who had received the inactivated polio vaccine (IPV) alone or in combination with either 1 other vaccine (<3 group) or 4 other vaccines (>4 group). Each of the 2 groups was subdivided into 2 subgroups in which Tdap was present or absent. Results: The >4 group was associated with a higher proportion of polio seroconversions than the <3 group (95% vs. 58%, respectively, p  < 0.01). Analysis of the <3 subgroup that excluded Tdap vs. the >4 subgroup that excluded Tdap showed no difference between them ( p  > 0.1). However, the >4 subgroup that included Tdap had significantly more seroconversions than either the <3 subgroup that excluded Tdap or the >4 subgroup that excluded Tdap ( p  < 0.01). Overall, at least 98% of subjects were at or above the putative level of seroprotection both pre- and post-vaccination, yet at least 81% of subjects seroconverted. In an analysis of 400 of the subjects in which clinic in- and outpatient encounters were counted over the course of 1 year following vaccinations, there was no significant difference between the 2 groups ( p  > 0.1). Conclusion: A combination of >4 vaccines including IPV appeared to have an immunopotentiation effect on polio seroconversion, and Tdap in particular was a strong candidate for an important role. The dose of IPV we studied in our subjects, who already had a high level of seroprotection, acted as a booster. In addition, there appear to be no negative health consequences from receiving few versus more multiple simultaneous vaccinations.